Self Adjustment Processes of UMSIDA Students in HIMMPAS Organization: Proses Penyesuaian Diri Mahasiswa UMSIDA di Organisasi HIMMPAS - Laili Yusriah; Ramon Ananda Paryontri (Academia Open, 2025)
General Background Entering a new organizational environment requires individuals to develop self-adjustment processes to manage personal demands, social expectations, and environmental pressures. Specific Background University students who join student activity units with complex structures and diverse cultural backgrounds, such as the HIMMPAS organization at Universitas Muhammadiyah Sidoarjo, encounter distinct challenges related to social interaction, physical demands, and organizational rules. Knowledge Gap Previous studies on student self-adjustment have predominantly employed quantitative approaches, resulting in limited exploration of students’ lived experiences and personal meaning-making processes within student organizations. Aims This study aims to analyze the self-adjustment experiences of UMSIDA students who participate in the HIMMPAS student activity unit. Results The findings reveal that students demonstrated self-adjustment through adaptation, conformity, and mastery, as reflected in their ability to manage social interactions, comply with organizational norms, and regulate personal behavior when facing demands and tensions. Although minor social interaction constraints were identified in one participant, both participants showed constructive responses toward organizational challenges. Novelty This study provides an in-depth phenomenological account of student self-adjustment within a nature-lover student organization context. Implications The findings contribute to a deeper understanding of student adjustment processes in extracurricular organizations and may inform the development of supportive organizational environments in higher education institutions. Highlights: Participants demonstrated varied personal strategies in managing organizational demands and social dynamics. Behavioral regulation supported students in responding constructively to internal and external pressures. Lived experiences revealed meaningful adaptation within a complex extracurricular setting. Keywords: Self Adjustment, Phenomenological Study, Student Organization, Himmpas, University Students